Comparative study of permanent-magnet vernier motor and interior permanent-magnet motor for hybrid electric vehicles - Cao, Libing (2023)
In this paper, a comparative study of permanent-magnet vernier (PMV) motors and the interior permanent-magnet (IPM) motor for hybrid electric vehicles (HEVs) is presented. Four different topologies of PMV motors, including the conventional PMV motors and the developed U-shape PMV (U-PMV) motors with full-pitch (FP) and short-pitch (SP) windings, are comprehensively investigated and compared. The results show that higher torque and PM utilization can be achieved in the developed U-PMV motors due to the improved flux modulation effect. In addition, SP windings can facilitate PMV motors to achieve higher output torque/power, efficiency, and PM utilization when a high power factor is required. The improvement of the flux modulation effect in the developed U-PMV motors is explained using the simplified magnetic circuit, while the advantages of SP winding over FP winding at a high power factor level are illustrated using winding function theory. To evaluate the performances and potential of PMV motors for HEVs, both the conventional PMV and the developed U-PMV motors are optimized and compared with the IPM motor under fair conditions. The results show that PMV motors offer higher torque density, power density, and lower torque ripples, compared to the IPM motor. However, more PM consumption and higher cost of PMV motors are the disadvantages of PMV motors for automotive applications where cost constraints are sensitive.